Covid 19 Response: President Rouhani And President Raisi's Policy Narrative In Iran Through The Media - Joevi Roedyati; Rino Febrianno Boer; Nizvi Varra Azqiya (Publikasi Indonesia, 2022)
In the midst of political and economic sanctions obtained from the United States, Iran had to fight the Covid-19 pandemic which has killed thousands of people in Iran, placing Iran in a chaotic situation due to the initial handling that did not go well. Now President Raisi is taking over the Iranian crisis by issuing new policies related to handling Covid-19 and improving the situation and conditions of people who have lost their trust in the Iranian Government. This research wants to examine the narratives launched by the Government of Iran through the media regarding the policy of dealing with Covid-19. By using the discourse analysis method, this study tries to explore the contents of the narrative and explore what discourse the Iranian government wants to convey to the public.